EFL students’ self-regulated online learning in the expository and analytical writing course - Salsabila, Firnanda (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
The online learning environment provides a flexible learning environment where the students can learn anytime and anywhere despite the distance. Since the teaching and learning process shifts into online learning, the students should be able to manage their learning process by themselves. Implementing self-regulated online learning could help the students to be responsible for their learning process to achieve good academic performance. Several previous studies already discussed the implementation of self-regulated online learning across four language skills; listening, speaking, reading, and writing. However, in writing courses, the previous studies did not mention the specific writing text applied in self-regulated online learning. This study aimed to identify the frequency of the undergraduates’ use of forethought phase, performance phase, and self-reflection phase in self-regulated online learning toward expository and analytical writing course. The instrument used in this study was the OSEL Questionnaire which consisted of three phases: forethought phase, performance phase, and self-reflection phase. The subject enrolled in this study were 46 students from the freshmen class of the English Education program at one state university in Indonesia. In general, the result showed that three phases in self-regulated online learning toward expository and analytical writing course have medium means which were above 3.00. Only task strategies that had the lowest mean from all the sub-points were presented. Further discussion will explain previous studies and theories that support the finding of this research.